2010
DOI: 10.1053/j.gastro.2009.08.064
|View full text |Cite
|
Sign up to set email alerts
|

The Hormone Receptor GUCY2C Suppresses Intestinal Tumor Formation by Inhibiting AKT Signaling

Abstract: Background & Aims-Gucy2c is the intestinal cell receptor for the paracrine hormones guanylin and uroguanylin that converts GTP to cyclic (c)GMP. It functions as a tumor suppressor; its loss

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
198
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 107 publications
(206 citation statements)
references
References 46 publications
(86 reference statements)
8
198
0
Order By: Relevance
“…Regulation of PTEN by cGMP/PKG2 signaling is likely because the total PTEN levels were affected by PKG2 expression and activation. These results are consistent with a previous study in HCT116 colon cancer cells, 29 but the precise relationship between PKG2 and PTEN has yet to be elucidated. PTEN activity plays an important role downstream of PKG2 because knockdown of PTEN expression blocked the inhibitory effect of PKG2 on phospho-AKT in colon cancer cells.…”
Section: Pkg2 Activates Foxo3a In the Colonsupporting
confidence: 83%
See 4 more Smart Citations
“…Regulation of PTEN by cGMP/PKG2 signaling is likely because the total PTEN levels were affected by PKG2 expression and activation. These results are consistent with a previous study in HCT116 colon cancer cells, 29 but the precise relationship between PKG2 and PTEN has yet to be elucidated. PTEN activity plays an important role downstream of PKG2 because knockdown of PTEN expression blocked the inhibitory effect of PKG2 on phospho-AKT in colon cancer cells.…”
Section: Pkg2 Activates Foxo3a In the Colonsupporting
confidence: 83%
“…29 The results shown herein extend our understanding of this phenomenon by demonstrating that PKG2 mediates AKT inhibition downstream of cGMP in this pathway. Independent work has shown that PKG2 also suppresses AKT in gastric cancer cell lines, where the mechanism was suggested to occur at the level of receptortyrosine kinases because ERK was also inhibited.…”
Section: Pkg2 Activates Foxo3a In the Colonsupporting
confidence: 47%
See 3 more Smart Citations